![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(x-5\right)-\frac{1}{3}=\frac{2}{5}\)
\(\Rightarrow\left(x-5\right)=\frac{2}{5}+\frac{1}{3}\)
\(\Rightarrow\left(x-5\right)=\frac{11}{15}\)
\(\Rightarrow x-5=\frac{11}{15}\)
\(\Rightarrow x=\frac{11}{15}+5\)
\(\Rightarrow x=\frac{86}{15}\)
b) \(\frac{2}{3}\cdot x-\frac{3}{2}\cdot x=\frac{5}{12}\)
\(\Rightarrow x\cdot\left(\frac{2}{3}-\frac{3}{2}\right)=\frac{5}{12}\)
\(\Rightarrow x\cdot\left(-\frac{5}{6}\right)=\frac{5}{12}\)
\(\Rightarrow x=\frac{5}{12}:\left(-\frac{5}{6}\right)\)
\(\Rightarrow x=-\frac{1}{2}\)
c) \(-\frac{2}{3}\cdot x+\frac{1}{5}=\frac{3}{10}\)
\(\Rightarrow-\frac{2}{3}\cdot x=\frac{3}{10}-\frac{1}{5}\)
\(\Rightarrow-\frac{2}{3}\cdot x=\frac{1}{10}\)
\(\Rightarrow x=\frac{1}{10}:\left(-\frac{2}{3}\right)\)
\(\Rightarrow x=-\frac{3}{20}\)
d) \(4-\left(\frac{1}{2}\cdot x+\frac{3}{4}\right)=-\frac{1}{5}\)
\(\Rightarrow\left(\frac{1}{2}\cdot x+\frac{3}{4}\right)=4-\left(-\frac{1}{5}\right)\)
\(\Rightarrow\)\(\frac{1}{2}\cdot x+\frac{3}{4}=\frac{21}{5}\)
\(\Rightarrow\)\(\frac{1}{2}\cdot x=\frac{21}{5}-\frac{3}{4}\)
\(\Rightarrow\)\(\frac{1}{2}\cdot x=\frac{69}{20}\)
\(\Rightarrow\)\(x=\frac{69}{20}:\frac{1}{2}\)
\(\Rightarrow\)\(x=\frac{69}{10}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
GIẢI
a)5/x = -3/2 + 4/3
5/x = -9/6 + 8/6
5/x = -1/6
=> x = 5 × 6 : -1
=> x = -30
b) x/-1 + 5/9 = -1/3
x/-1 = -1/3 - 5/9
x/-1 = -3/9 - 5/9
x/-1 = -8/9
=> x = (-8 ) × ( -1 ): 9
=> x = 8/9
HỌC TỐT ^_^
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{2}{3}-\frac{1}{5}.\left(\frac{3.x}{2}-\frac{1}{4}\right)=\frac{11}{2}-\frac{1}{4}\)
\(\Leftrightarrow\frac{2}{3}-\frac{1}{5}.\left(\frac{3.x}{2}-\frac{1}{4}\right)=\frac{21}{4}\)
\(\Leftrightarrow\frac{1}{5}.\left(\frac{3.x}{2}-\frac{1}{4}\right)=\frac{2}{3}-\frac{21}{4}\)
\(\Leftrightarrow\frac{1}{5}.\left(\frac{3.x}{2}-\frac{1}{4}\right)=\frac{-55}{12}\)
\(\Leftrightarrow\frac{3.x}{2}-\frac{1}{4}=\frac{-55}{12}:\frac{1}{5}\)
\(\Leftrightarrow\frac{3.x}{2}-\frac{1}{4}=\frac{-275}{12}\)
\(\Leftrightarrow\frac{3.x}{2}=\frac{-275}{12}+\frac{1}{4}\)
\(\Leftrightarrow\frac{3.x}{2}=\frac{-68}{3}\)
\(\Leftrightarrow\left(3.x\right).3=-136\)
\(\Leftrightarrow3.x=-136:3\)
\(\Leftrightarrow3.x=\frac{-136}{3}\)
\(\Leftrightarrow x=\frac{-136}{3}:3\)
\(\Leftrightarrow x=\frac{-136}{9}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(2x-1\right)^2-25=0\)
\(\left(2x-1\right)^2=0+25=25\)
\(\left(2x-1\right)^2=5^2=\left(-5\right)^2\)
\(\Rightarrow\left[\begin{array}{nghiempt}2x-1=5\\2x-1=-5\end{array}\right.\Rightarrow\left[\begin{array}{nghiempt}2x=6\\2x=-4\end{array}\right.\Rightarrow\left[\begin{array}{nghiempt}x=3\\x=-2\end{array}\right.\)
b) \(8x^3-50x=0\)
\(2x\left(4x^2-25\right)=0\)
\(\Rightarrow\left[\begin{array}{nghiempt}2x=0\\4x^2-25=0\end{array}\right.\Rightarrow\left[\begin{array}{nghiempt}x=0\\4x^2=25\Rightarrow x^2=\frac{25}{4}\Rightarrow\left[\begin{array}{nghiempt}x=\frac{5}{2}\\x=-\frac{5}{2}\end{array}\right.\end{array}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,TH1:x-2021=0=>x=2021\)
\(Th2:x-2022=0=>x=2022\)
Vậy \(x\in\left\{2021;2022\right\}\)
\(b,x\left(8-5\right)=1080\)
\(x.3=1080\)
\(x=360\)
\(c,x^3=216< =>6^3=216=>x=3\)
\(d,5^5=3125\)
a) ( x- 2021) * ( x- 2022) = 0
=> \(\orbr{\begin{cases}x-2021=0\\x-2022=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=2021\\x=2022\end{cases}}}\)
b) b. 8x - 5x = 2022
=> 3x = 2022
=> x = 674
c) \(5\cdot x^3=1080\)
=> \(x^3=216\)
=> \(x^3=6^3\)
=> x = 6
d) \(5^x=3125\)
=> \(5^x=5^5\)
=> x = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
1) (3x-1)(-1/2x+5)=0
TH1: 3x-1=0
3x = 1
x = 1/3
TH2: -1/2x+5=0
-1/2x =-5
x = 10
2) (3/4-x)^3=-8
(3/4-x)^3=(-2)^3
=> 3/4-x=-2
x=3/4+2
x= 11/4
3) |2x-1|=-4^2
|2x-1|=16
=> 2x-1=-16 hoặc 2x-1=16
TH1: 2x-1=-16
2x =-15
x = -15/2
TH2: 2x-1=16
2x =17
x = 17/2
\(\dfrac{2}{5}x-\dfrac{1}{5}x=\dfrac{3}{4}\)
\(\left(\dfrac{2}{5}-\dfrac{1}{5}\right)x=\dfrac{3}{4}\)
\(\dfrac{1}{5}x=\dfrac{3}{4}\)
\(x=\dfrac{3}{4}:\dfrac{1}{5}=\dfrac{15}{4}\)
\(\dfrac{2}{5}.x-\dfrac{1}{5}.x=\dfrac{3}{4}\)
\(x.\left(\dfrac{2}{5}-\dfrac{1}{5}\right)=\dfrac{3}{4}\)
\(x.\dfrac{1}{5}\) = \(\dfrac{3}{4}\)
\(x\) = \(\dfrac{3}{4}:\dfrac{1}{5}\)
\(x\) \(\dfrac{15}{4}\)